Taxonomic notes on Amemboa lyra Paiva and Amemboa riparia Polhemus & Andersen (Hemiptera: Heteroptera: Gerridae) - Polhemus, J. T.; Tran, A. D. (Zootaxa, 2012)
Amemboa ripiaria Polhemus & Andersen, 1984 was recognised as junior synonym of Amemboa lyra (Paiva, 1918) byZettel & Chen (1996). After examination of a series of Amemboa specimens from Myanmar, we now determine that thesetwo names are not synonymous and thus re-establish Amemboa riparia. These species can be separated from each other by the structures of the male’s fore leg, and the apical part of the pygophore.